A king translated: the writings of King James VI & I and their interpretation in the Low Countries, 1593 - 1603 - Stilma, Astrid (St Andrews studies in reformation history, 2012)
Publishers and translators -- Translation -- The Battle of Lepanto -- Basilikon doron -- Meditations -- Daemonologie